2001
DOI: 10.3759/tropics.10.427
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Dynamics of Phytophagous Lady Beetle Populations under Different Climate Conditions in Sumatra and Java, Indonesia.

Abstract: Since 1990 we have studied population dynamics of the phytophagous lady beetles, Epilachna vigintioctopunctata, E. enneasticta and Epilachna sp. 3 (aff. emarginata), (Coleoptera: Epilachninae) in Padang, Sukarami (West Sumatra), Bogor (West Java) and Purwodadi (East Java), Indonesia. These sites have distinctly different climate conditions, e.g. Padang has a typical tropical rainforest climate without a clear alternation of wet and dry seasons, while Purwodadi has a strong dry season of 6-7 months. We have con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…As a whole, the degree of adaptation to centro of the Bogor populations of H. vigintioctopunctata fluctuated but gradually increased from year to year with regards to both adult feeding preference for, and ability of larvae to develop on, this novel host, without obvious decrease in the ability to use the normal host S. torvum (Figs ). Given that H. vigintioctopunctata has eight generations at most per year in Indonesia (Nakamura et al ), this evolutionary change of the host specificity took place during about 50 or less generations. It is difficult to predict that the adaptation to centro by the Bogor populations will further proceed and result in the establishment of a generalist on solanaceous plants and centro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a whole, the degree of adaptation to centro of the Bogor populations of H. vigintioctopunctata fluctuated but gradually increased from year to year with regards to both adult feeding preference for, and ability of larvae to develop on, this novel host, without obvious decrease in the ability to use the normal host S. torvum (Figs ). Given that H. vigintioctopunctata has eight generations at most per year in Indonesia (Nakamura et al ), this evolutionary change of the host specificity took place during about 50 or less generations. It is difficult to predict that the adaptation to centro by the Bogor populations will further proceed and result in the establishment of a generalist on solanaceous plants and centro.…”
Section: Discussionmentioning
confidence: 99%
“…Henosepilachna vigintioctopunctata is multivoltine, having at most eight generations per year in Indonesia (Nakamura et al ). Adults and larvae feed on leaves of the same plant species.…”
Section: Methodsmentioning
confidence: 99%
“…Population censuses of different life-history stages (egg, third-instar larvae, fourth-instar larvae, pupae, teneral adults and mature adults) were made at 3-7 day intervals over a period of 37 months from January 1982 to January 1985 at Padang and for almost 10 years between 1991 and 2000 at Sukarami. Full details of the field sites and sampling techniques are given in Nakamura et al (1990Nakamura et al ( , 2001). Life-history experiments in the laboratory have shown that there are differences in life histories between the sites.…”
Section: Ladybeetle Time-seriesmentioning
confidence: 99%
“…As part of a long-term study on the insect fauna of Indonesia ( Inoue et al , 1993;Nakamura et al , 2001;Sota et al , 2001 ) the population dynamics and life tables of a number of tropical beetles have been intensively monitored ( Abbas & Nakamura, 1985;Nakamura et al , 1988Nakamura et al , , 1989Nakamura et al , , 1990Noerdjito & Nakamura, 1999 ). With the availability of such long-term population dynamic data, the broad objective in this study therefore is to explore processes and identify the mechanisms leading to the population fluctuations in two lady beetles ( Epilachna vigintioctopunctata Coleoptera: Coccinellidae: Epilachninae and Epilachna enneasticta Coleoptera: Coccinellidae: Epilachninae) from western Indonesia.…”
Section: Introductionmentioning
confidence: 99%